Development, exploration and optimization of porous titanium and titanium alloys: A review - Baoguang Zhang; Kun Yang; Lei Shen; Xingyu Duan; Shaoyang Zhao; Wenbin Gao; Chenyang Xu; Jian Wang (Journal of Science: Advanced Materials and Devices)
As an integrated material of structure and function, porous titanium (Ti) and Ti alloys with a porosity of (10–95%) processes a wide application prospect in many fields. However, they still faced some issues, including the design and optimization of pore structure, the improvement of service performance, and the exploration of unique applications. To provide valuable insights into addressing these issues, the recent advances in porous Ti and Ti alloys have been reviewed systematically. Firstly, the manufacturing technologies for porous Ti and Ti alloys were expounded and objectively evaluated, with a focus on comparing the corresponding pore structures and mechanical properties. Besides, the current applications corresponding mechanisms, and characteristics of porous Ti and Ti alloys were introduced in detail. Finally, as key factors determining the performance and functions of porous Ti and Ti alloys, the design and optimization of pore structure and doping modification were emphatically summarized and discussed.